Bringing the elephant into the room? Enacting conflict in collective prosocial organizing - Powell, E. Erin; Hamann, Ralph; Bitzer, Verena; Baker, Ted (Journal of Business Venturing, 2018)
Cross-sector partnerships have the capacity to bring together partners from very different backgrounds and circumstances toward collective prosocial efforts. We conducted a longitudinal inductive field study of eight cross-sector partnerships formed as new ventures addressing a variety of fundamental social challenges in the context of deep inequality in post-Apartheid South Africa. This allowed us to develop theory and a process model that explains how some partnerships are able to achieve collective prosocial efforts while others engage in only one-sided efforts or become inactive. The key differences hinge on processes of enacting or failing to enact conflicting material interests among relevant stakeholders. Our results have implications for the inclusion of material interests in theories of cross-sector partnering and for our understanding of entrepreneurship under conditions of inequality. The theory we develop provides a platform for future research on collective prosocial organizing in the contexts that need it most.